ANALISIS FAKTOR - FAKTOR YANG MEMENGARUHI RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - ENJELI DIVER; REALIZE . (JURNAL ILMIAH KOHESI, 2020)
The main purpose of an investor‟s investment is to achieve a high return. And when insvestor‟s want to invest in the capitalmarket, investors will evaluate the company‟s performance to determine which shares will provide benefits. Companies withgood performance will certainly make investors more interested because the company‟s performance affects stock prices.And the manufacturing industry sub-sector chosen as the object of research is food and baverage. The purpose of thisresearch is to analyze the effect of Return On Asset (ROA), Debt to Equity Ratio (DER), Price Earning Ratio (PER), andEarning Per Share (EPS) on stock return on manufacturing companies in the food and baveragesub sector. Listed on theIndonesia stock exchange for the period 2015-2019. The sampling method used is purposive sampling, there are 10companies that have met the required sample criteria with a period of 5 years. Hypothesis testing uses multiple linearregression analysis using statistical applications test and hypothesis testing. Partially the results of the study indicate thatReturn On Asset (ROA) significantly influence stock return, but in the variable Debt to Equity Ratio (DER), Price EarningRatio (PER), and Earning Per Share (EPS) shows that there is no significant effect on stock return. Silmutaneously theresults of the study show that Return On Asset (ROA), Debt to Equity Ratio (DER), Price Earning Ratio (PER), and EarningPer Share (EPS) together have a significant effect on stock return.